Dr. Nyindem Nancy Sirih-Nagang and Dr. Eric Anchimbe on linguistic dynamics during the ongoing crisis in Cameroon - Sirih-Nagang, Nyindem Nancy; Anchimbe, Eric (Cluster Conversations, 2025)
In this episode of the Cluster Conversations, fellow Dr. Nyindem Nancy Sirih-Nagang talks with her host Dr. Eric Anchimbe about her research on the linguistic dynamics in the ongoing violent crisis in Cameroon. It exposes the creation of new lexemes and describes the linguistics and non-linguistic techniques employed in communicating through the labelling of concepts, individuals, or situations by the ruling government and the secessionist fighters or activists of the two Anglophone regions in Cameroon.